EMPLOYEE UNDERSTANDING OF THE DIGITALIZATION ERA AND ITS IMPACT ON WORK ENGAGEMENT: A QUALITATIVE STUDY AT LPD SEMSEMAN - Suciyawati, Ni Putu; Putra, Made Pramana; Nugraha, Putu Ananda Devi (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
Digitalization has significantly changed various sectors, including rural financial institutions like LPD Semseman. This study explores employees’ understanding of digitalization and its impact on work engagement at LPD Semseman. Using a descriptive qualitative approach with a case study design, ten employees were purposively selected based on their direct involvement with digital technology and employment tenure of over one year. Data were collected through in-depth interviews, observation, and document review, and then analyzed thematically. The results show that LPD Semseman employees generally recognize the importance of digitalization in supporting daily operations and services. Adopting digital tools like the LPD Mobile application and QRIS payment system has streamlined work processes, improved efficiency, and reduced manual workload. While initial adaptation was challenging, especially for senior employees, regular training provided by the organization has successfully enhanced digital literacy for all staff. Younger, more technologically adept employees have been key in assisting their senior colleagues during the transition. Digitalization has also increased work engagement, reflected in higher motivation, a stronger sense of belonging, and improved job satisfaction. Supporting factors include a collaborative work culture, ongoing training, and organizational recognition. The main obstacles encountered at the outset were limited digital literacy and resistance to change, addressed through organizational support and intensive training. This study highlights the importance of developing digital literacy and maintaining organizational support to enhance employee engagement in the digital era.